👤

(3x4+x5)-(12:3+20:4)+2x5-6=

Respuesta :

Respuesta:

[tex]\left(3x\cdot \:4+x\cdot \:5\right)-\left(\frac{12}{3}+\frac{20}{4}\right)+2x\cdot \:5-6=27x-15[/tex]

Explicación paso a paso:

[tex]\left(3x\cdot \:4+x\cdot \:5\right)-\left(\frac{12}{3}+\frac{20}{4}\right)+2x\cdot \:5-6\\=3x\cdot \:4+x\cdot \:5-\left(\frac{12}{3}+\frac{20}{4}\right)+2x\cdot \:5-6\\=12x+5x-9+10x-6\\=12x+5x+10x-9-6\\=27x-9-6\\=27x-15[/tex]

[tex](3 \times 4 + 4 \times 5) - (12 \div 3 + 20 \div 4) + 2 \times 5 - 6[/tex]

[tex](12 + 20) - (4 + 5) + 10 - 6[/tex]

[tex]32 - 9 + 4[/tex]

[tex]23 + 4[/tex]

[tex]27[/tex]